2020
DOI: 10.7554/elife.52962
|View full text |Cite
|
Sign up to set email alerts
|

A complex regulatory landscape involved in the development of mammalian external genitals

Abstract: Developmental genes are often controlled by large regulatory landscapes matching topologically associating domains (TADs). In various contexts, the associated chromatin backbone is modified by specific enhancer–enhancer and enhancer–promoter interactions. We used a TAD flanking the mouse HoxD cluster to study how these regulatory architectures are formed and deconstructed once their function achieved. We describe this TAD as a functional unit, with several regulatory sequences acting together to elicit a trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 84 publications
2
42
0
Order By: Relevance
“…7 C,D). In agreement, recent in vivo studies revealed that the patterning activity of HOX13 paralogs during limb and genital development relies on their ability to increase accessibility at specific sites ( Desanlis et al, 2020 ; Amandio et al, 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…7 C,D). In agreement, recent in vivo studies revealed that the patterning activity of HOX13 paralogs during limb and genital development relies on their ability to increase accessibility at specific sites ( Desanlis et al, 2020 ; Amandio et al, 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…Interestingly, binding of HOX13 to initially inaccessible chromatin was observed at the enhancer referred to as Prox, which drives Hoxd expression in the genital bud 23 (referred to as Prox in ref. 23 ), raising the possibility that HOX13 pioneering action may not be limited to the developing limb but rather a general feature of HOX13dependent developmental programs. Whether other HOX factors implement their specific developmental program by changing the chromatin accessibility landscape remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Expectedly, stronger phenotypes were obtained by deleting the ZRS enhancer region, as this sequence is the only known limb enhancer in this landscape (Lettice et al, 2017;Paliou et al, 2019;Williamson et al, 2019). The transitory effects observed when modifying T-DOM could either reflect a normal enhancer deployment delayed by changes in the 3D context or, alternatively, a novel organisation in enhancer-promoter interaction due to the known cooperative capacity that neighbouring enhancers can display during embryonic development (Amândio et al, 2020;Bolt and Duboule, 2020;Osterwalder et al, 2018). Similarly, the deletion of the TAD border and inversion of the regulatory domain at the Sox9/Kcnj2 locus only had mild effects on gene expression (Despang et al, 2019).…”
Section: Enhancers Topology and Regulatory Heterochroniesmentioning
confidence: 99%
“…In this context, topologically associating domains (TADs) were defined as genomic intervals where chromatin interactions tend to take place more frequently than with adjacent regions (Dixon et al, 2012;Nora et al, 2012) and such domains are frequently understood as functional units that host enhancers and their target promoters (Furlong and Levine, 2018). Indeed, some key developmental genes are found under the control of regulatory domains that are contained within TADs, which harbour tissue-specific regulatory sequences or multiple acting enhancers that confer robustness and resilience (Amândio et al, 2020;Montavon et al, 2011;Osterwalder et al, 2018;Sagai et al, 2009;Will et al, 2017).…”
Section: Introductionmentioning
confidence: 99%